MANAGING DUAL DEMANDS IN HIGHER EDUCATION: A QUALITATIVE STUDY OF WORK–LIFE BALANCE AND PERCEIVED ACADEMIC EMERGENCY RESPONSE EFFICIENCY AMONG INTERNATIONAL PART-TIME MASTER’S STUDENTS FROM CHINA - Zhang , Chuang; Lingaiah, Jayasri; Bai , Kecheng (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
This study aimed to investigate how work-life balance, employment type, and time management skills affect perceived academic emergency response efficiency (PERE) among international Chinese students who are enrolled in a part-time master’s degree at a private university in Malaysia. Interviews with ten participants indicated that flexible working hours and careful planning help students to effectively respond when unexpected academic demands surface. In contrast, strict work schedules, sudden demands, and issues maintaining work-life balance potentially lowered their confidence in responding to such situations. Based on the role strain theory, the findings indicate that many students experience parallel pressures from their professional roles, academic responsibilities, and family commitments. Organised time management, flexible arrangements at the workplace, and supportive academic environments are among the practices that appear to help students cope and respond to academic challenges more effectively. Although the study is conducted in Malaysia, the issues highlighted reflect challenges commonly faced by working international postgraduate students in many countries and offer useful insights for institutions that support this group. The findings contribute to understanding how structural and individual factors interact in shaping students’ academic responsiveness in higher education contexts.